1998
DOI: 10.1016/s0006-3495(98)77598-8
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding of Acrylodan-Labeled Human Serum Albumin Probed by Steady-State and Time-Resolved Fluorescence Methods

Abstract: Steady-state and time-resolved fluorescence spectroscopy was used to follow the local and global changes in structure and dynamics during chemical and thermal denaturation of unlabeled human serum albumin (HSA) and HSA with an acrylodan moiety bound to Cys34. Acrylodan fluorescence was monitored to obtain information about unfolding processes in domain I, and the emission of the Trp residue at position 214 was used to examine domain II. In addition, Trp-to-acrylodan resonance energy transfer was examined to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
185
3
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(220 citation statements)
references
References 30 publications
31
185
3
1
Order By: Relevance
“…Anisotropy plots for each component showed clearly that this was a single step transition between the native and the unfolded states, because the anisotropy change was the same for each emitter. This agreed with previously published results [53,54], for example, initial (0M)/final (4M) anisotropy ratios (~1.7) for both Trp components were close the mean lifetime ratio (1.9) from Flora et al [17] Comparing the MCR scores (Figure 3, and SI, Fig. S-12/13) shows very different behavior and it was interesting to note that the Comp3 (RTP) contribution increased in a sigmoidal fashion (centered at 2M GuHCl) as GuHCl concentration increased.…”
Section: Page 13 Of 26supporting
confidence: 93%
See 3 more Smart Citations
“…Anisotropy plots for each component showed clearly that this was a single step transition between the native and the unfolded states, because the anisotropy change was the same for each emitter. This agreed with previously published results [53,54], for example, initial (0M)/final (4M) anisotropy ratios (~1.7) for both Trp components were close the mean lifetime ratio (1.9) from Flora et al [17] Comparing the MCR scores (Figure 3, and SI, Fig. S-12/13) shows very different behavior and it was interesting to note that the Comp3 (RTP) contribution increased in a sigmoidal fashion (centered at 2M GuHCl) as GuHCl concentration increased.…”
Section: Page 13 Of 26supporting
confidence: 93%
“…Here, the second option was more probable, as reports have shown that there was a decreased Trp lifetime for HSA denaturation due to increased solvent exposure after recovery from thermal denaturation. The increased anisotropy was ~11% which was the same as the mean lifetime decrease of 5.28 to 4.72 ns recorded by Flora et al [17]. This was supported by evaluation of MCR scores (Figure 3) where Comp4 scores were always much less after refolding which indicated higher quenching due to solvent exposure.…”
Section: Refolded Structure Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…When GuHCl is used to induce protein unfolding in serum albumins it has led to the reporting of contradictory results in the literature with regard to the exact unfolding mechanism. There are reports that point induced unfolding HSA occurs in a single step [13,[21][22][23][24] while other studies indicate a multi-step process with the formation of stable intermediates [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%